FROM THE CULTURAL MISSION TO THE INTERNATIONAL PROJECTION OF CULTURE. MEXICO’S CULTURAL DIPLOMACY (1900-2000) (Tzintzun, Revista de Estudios Históricos, 2022)
The projection of a country’s culture abroad is a characteristic action of what iscalled cultural diplomacy; many countries have used cultural diplomacy strategiesto promote their identity, values, symbols, traditions, lifestyles, as well as themost outstanding artistic manifestations to position it as an admirable country,in such a way as to generate a favorable climate for cooperation and businesswith countries which maintains relations. The purpose of this article is toinvestigate the relevant milestones of Mexico’s cultural diplomacy throughoutthe 20th century. Thus, taking the Mexican case as an example, we intend toshow how the cultural component in foreign policy contributed to reaffirm thecountry’s international prestige.
Keywords: cultural diplomacy; Mexico; culture,}; culture; soft power; public diplomacy